Evaluación Presupuestaria al Gobierno Autónomo Descentralizado Parroquial Cangonamá, del Cantón Paltas, de la Provincia de Loja, periodo 2022. - Pardo Quezada, Luis Andrés (2024)
The purpose of this Curricular Integration Work entitled "Budgetary Evaluation of the Decentralized Autonomous Government of the Cangonamá Parish, of the Paltas Canton, of the Province of Loja, period 2022", aims to follow the proposed goal, which consists of carrying out a budget evaluation in the GAD Cangonamá in the period 2022. The work was developed with a mixed approach, exploratory-descriptive, and the application of research methods and techniques. The results obtained based on the application of budget management indicators, let us know that the activities, programs and projects established within the Annual Operating Plan were not completed in their entirety, demonstrating that of the seven projects planned for the year 2022, two of them have not been executed in any percentage, In the same way, the efficiency and effectiveness in the management and use of the institution's financial resources was evaluated, using budget management indicators to determine if the established goals and objectives were met, obtaining an execution level of 75.84% for income and 57.87% for expenses. Finally, a report was prepared in which the most relevant results are recorded, as well as conclusions and recommendations that will serve for timely decision-making within the entity, evidencing that the Parish GAD does not carry out budgetary evaluations, which prevented measuring the management carried out, it was also evidenced that those in charge of the POA, They do not have the necessary knowledge for it to carry out an appropriate structure, planning and orientation, affecting the allocation of resources according to their objectives and goals.